The Position of "Al-Mufiid" Among Sarf Books (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article is dedicated to examining the position of Mahmud ibn Umar az-Zamakhshari’s book Al-Mufid fi at-Tasrif in the history of Arabic morphology (sarf). The work is concise and covers the fundamental topics of sarf, written in a simplified style for students. However, unlike Zamakhshari’s other works, it did not gain widespread recognition and has survived in very few copies. This study analyzes the book’s structure, methodology, and significance in the field of sarf based on its only known manuscript. Additionally, it provides a detailed description of the manuscript, its errors, and the methodology used for preparing the text for scholarly publication.